The Influence of Critical Soft Factors on Quality Improvement and Organizational Performance : Evidence of Malaysia's Electrical and Electronics Sector - Abdullah, Muhammad Madi; Uli, Jegak; Ismail, Maimunah; Ahmad, Shamsuddin (2007)
Quality management (QM) is considered to be an important management philosophy that sustains organizations towards continuous quality improvement (QI) and customer satisfaction. The conventional wisdom is that quality improvement leads to higher revenues, decreased costs, and increased profits. This paper examines the influence of the critical soft factors (CSFs) on QI practice and organizational performance. The following soft factors were found to have significant influence on QI practice: management commitment, customer focus, employee involvement, training and education, as well as reward and recognition. Organizational performance was significantly influenced by the following soft factors: management commitment, customer satisfaction, employee involvement, and reward and recognition. QI was positively related to organizational performance.